The Impact of Interparental Conflict on Children's Attention and Memory Performance. Issue 2 (14th August 2020) - Zemp, Martina; Paetzold, Isabell; Milek, Anne
Abstract : Background: Previous research suggests that exposure to interparental conflict may affect children's attention and memory performance, but few studies have examined this hypothesis experimentally. Objective: The goal of this study was to address this gap by completing an experimental approach using audiotaped couple conflict simulations. Method: School classes of fifth‐ and sixth‐graders were randomly assigned to listen to one of the following three types of conversations: (a) an unresolved couple conflict, (b) a resolved couple conflict, or (c) a neutral couple conversation. Children's attention and memory performance were measured before and after stimulus exposure by performance tasks and their emotional insecurity was assessed by self‐report. Results: Children's emotional insecurity moderated the impact of the simulated couple conflict on their memory performance but not on attention. At low levels of emotional insecurity, children performed better in the memory task after hearing the unresolved couple conflict compared with the control group. Conclusion: Children's responses to simulated conflicts differ by a child's history of interparental conflict and conflict characteristics, such as whether arguments are resolved. Implications: Consideration of the family background is warranted when studying or treating child cognitive performance problems.